Rocket launches threaten global biodiversity conservation - Lee Ping Ang; Fanhao Kong; Enrique Hernández-Rodríguez; Qiuyu Liu; Carlos Cerrejόn; Mariano J. Feldman; Lei Shu; Li-Xin Ye; Lei Gao; Lee Ling Ang; Xiangbo Yin (Communications Earth & Environment, 2024)
Abstract Satellite technologies are essential for global conservation actions through providing continuous, real-time Earth monitoring. However, development of these technologies necessitates an increase in rocket launches, which introduces new threats to biodiversity. Here, we mapped rocket launch sites and assessed their threats on protected areas and terrestrial biodiversity. Our analysis revealed that over 90% launch sites are within areas where unprotected habitats excesses 50% and over 62% of operating sites are located within or near protected areas. The threats from rocket launches are potentially associated with biomes, coordinates, and proximity to oceans. In particular, threatened terrestrial species in Tropical and Subtropical Moist Broadleaf Forests are more vulnerable to these risks compared to species in other biomes. Without strategic planning, the continued growth of rocket launches could create conflicts between technological development and conservation efforts, undermining the achievement of UN Biodiversity Goals.